(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
Drivers belonging to groups 3 and 4 who, when analyzing accidents that occur at unregulated crossings of pedestrians, ignore the requirements of the relevant traffic rules, should be considered potentially guilty. It is possible to consider the movement of infantry from Group 3, which does not take into account the effect of the implicit risk factor as a human factor that is in co-existence.